2023
DOI: 10.3389/fonc.2023.1070019
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of neutrophil to lymphocyte ratio in gastric cancer patients receiving immune checkpoint inhibitors: a systematic review and meta-analysis

Abstract: BackgroundThe neutrophil to lymphocyte ratio (NLR) is a cost-effective and easily identifiable inflammatory biomarker that has been shown to be closely associated with tumor prognosis and predict survival in patients with multiple malignancies. However, the predictive value of NLR in patients with gastric cancer (GC) treated with immune checkpoint inhibitors (ICIs) has not been fully explored. Therefore, we conducted a meta-analysis to explore the potential of NLR as a predictor of survival in this population.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…A meta-analysis by Guo et al studying the dynamics of NLR during ICI treatment also showed that patients with a significant upward trend of NLR did not respond to immunotherapy, while those with a downward trend were associated with better clinical and treatment outcomes (16). Similarly, Zhang et al observed a significant correlation between NLR and ORR (p = 0.003) and a lack of significance between NLR and DCR (p = 0.111) in a meta-analysis involving patients with gastric cancer treated with immunotherapy (58).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…A meta-analysis by Guo et al studying the dynamics of NLR during ICI treatment also showed that patients with a significant upward trend of NLR did not respond to immunotherapy, while those with a downward trend were associated with better clinical and treatment outcomes (16). Similarly, Zhang et al observed a significant correlation between NLR and ORR (p = 0.003) and a lack of significance between NLR and DCR (p = 0.111) in a meta-analysis involving patients with gastric cancer treated with immunotherapy (58).…”
Section: Discussionmentioning
confidence: 91%
“…There is a paucity of literature that reported the association of NLR, PLR, and racial background in cancer patients treated with immune checkpoint inhibitors, while some studies that performed sub-group analysis according to country of origin reported contradicting results (58,83,84). However, sub-group analysis was not performed in this particular systematic review.…”
Section: Discussionmentioning
confidence: 99%
“… 21 Since neutrophils are one of the first responders to acute inflammation, NLR has been proposed as a prognostic predictor as well as an inflammatory marker in many diseases such as stroke, coronary artery disease, and various kinds of cancer. 6 7 8 22 Several studies have found high NLR and PLR values to be associated with a worse prognosis in neuro-otological diseases including Bell’s palsy and sudden sensorineural hearing loss. 23 24 25 Although NLR has been considered an inflammatory biomarker in peripheral vertigo, the usefulness of this parameter as a prognostic predictor remains inconclusive in AUV.…”
Section: Discussionmentioning
confidence: 99%
“…They have been identified as useful biomarkers for assessing the inflammatory response and for predicting the prognosis of various diseases such as stroke and various kinds of cancer. 6 7 8 Likewise, both NLR and PLR have been considered inflammatory biomarkers in patients with vestibulopathies such as benign paroxysmal positional vertigo and Meniere’s disease. 9 10 11 Previous studies have also investigated the role of NLR and PLR in AUV to determine its pathogenesis, but the results were inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…Our study comes in light of two previous meta-analyses that investigated the prognostic role of NLR in our target population. In their meta-analysis of nine studies, Zhang et al ( 52 ) found a significantly poorer OS for patients with high NLR but failed to find a significant relationship between high NLR and poor PFS. Within a short period of time after this study was published, Li et al ( 53 ) published another meta-analysis investigating the same group of patients in 10 studies.…”
Section: Discussionmentioning
confidence: 99%